Formulation and Evaluation of Moringa Polyherbal Shampoo - Bindage Rohan; Lohar Kiran; Mane Aditya; Chavan Dinesh; Todkar Rohit (Asian Journal of Pharmaceutical Research and Development, 2025)
The objective of this study is to develop and formulate an herbal shampoo using safe, natural ingredients, and to evaluate its physicochemical properties to ensure both safety and effectiveness. Shampoo is a hair care product designed to cleanse the hair by removing dirt, oil, dead skin cells, environmental pollutants, and other impurities that accumulate on the scalp and hair. This particular formulation is enhanced with herbal extracts and contains no synthetic additives. The herbal extracts included in the formulation are moringa, shikakai, aloevera, bringraj, neem, amla, hydroxy ethyl cellulose, a herbal shampoo was formulated using a simple mixing technique and subsequently evaluated for various physicochemical properties. The assessment methods included visual inspection, pH measurement, cleansing efficiency, determination of solid content percentage, dirt dispersion, foaming capacity, skin irritation.